Business modeling and software design : 5th International Symposium, BMSD 2015, Milan, Italy, July 6-8, 2015, Revised Selected Papers /: 5th International Symposium, BMSD 2015, Milan, Italy, July 6-8, 2015, Revised Selected Papers. ([2016]) - Unknown
No abstract available